Elective surgery system strengthening: development, measurement, and validation of the surgical preparedness index across 1632 hospitals in 119 countries - NIHR Global Health Unit on Global Surgery; COVIDSurg Collaborative; Konjanoska, Maja; Kavain, Snezhana B.; Kuzmanovska, Biljana; Lleshi, Albert; Kokareva, Anita; Kiprijanovska, Biljana; Trajkovska, Vanja; Nichevska, Marta; Gavrilovska Brzanov, Aleksandra; Burmuzoska, Marjana; et al. (Elsevier Ltd., 2022)
The 2015 Lancet Commission on global surgery identified surgery and anaesthesia as indispensable parts of holistic health-care systems. However, COVID-19 exposed the fragility of planned surgical services around the world, which have also been neglected in pandemic recovery planning. This study aimed to develop and validate a novel index to support local elective surgical system strengthening and address growing backlogs.